Impactos ambientales y externalidades asociadas al mejoramiento de servicios educativos en el instituto pedagógico Fray Florencio Pascual, Requena 2024 - Garcia Amaringo, Kelvin (2025)
The study, with a non-experimental, descriptive, analytical, correlational and cross sectional approach, evaluated the environmental impacts and social externalities derived from the improvement of educational services at the Higher Pedagogical Institute. With a sample of 52 intentionally selected interviews among teaching and administrative staff and members of the local community, data were collected through surveys with a structured questionnaire, which reached a Cronbach's Alpha reliability of 0.807 for 25 items. Since the data did not present a normal distribution (Kolmogorov-Smirnov test), the Spearman correlation coefficient was used for inferential analysis. The project implemented sustainable practices such as the use of eco-efficient materials, the restoration of green areas and environmental mitigation measures (recycling, energy optimization and awareness campaigns), managing to control negative impacts and promote responsible environmental management. These actions fostered ecological awareness and established a replicable model of sustainability. In the social sphere, educational improvements significantly increased the quality of teaching, expanded equity in access and generated opportunities for low-income students. In addition, the renovated infrastructure contributed to local economic development, generated employment and strengthened social cohesion through integrative programs that linked the institute with the community. The implementation of scholarships, workshops and strategic alliances consolidated social inclusion and guaranteed the sustainability of the project. The results highlight the importance of maximizing positive externalities to transform and improve the well being of the benefited community.